17-3x=19-4x

Simple and best practice solution for 17-3x=19-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-3x=19-4x equation:


Simplifying
17 + -3x = 19 + -4x

Solving
17 + -3x = 19 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
17 + -3x + 4x = 19 + -4x + 4x

Combine like terms: -3x + 4x = 1x
17 + 1x = 19 + -4x + 4x

Combine like terms: -4x + 4x = 0
17 + 1x = 19 + 0
17 + 1x = 19

Add '-17' to each side of the equation.
17 + -17 + 1x = 19 + -17

Combine like terms: 17 + -17 = 0
0 + 1x = 19 + -17
1x = 19 + -17

Combine like terms: 19 + -17 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 2x-7=-3x+18 | | 45-2m=3m-18 | | 18-p=-32 | | 3x-25=4x-16 | | -25-x=19 | | x^2-4kx+k+2=0 | | 2-4kx+k+2=0 | | 19-x=25 | | 7+2X=5X-2 | | 11x-1=13y+3 | | (1+m^2)*x^2-2*m*x+1-m^2=0 | | (lgx)3=3 | | 4m=19 | | (y-z)p+(z-x)q=x-y | | X(x+5)=336 | | 3x-2+5x=8-2x+20 | | f(x)=3x^2-18x+27 | | 12x=252 | | 2tan^2x+5tanx=0 | | X-29=47 | | x^2+11.91x=2083.67 | | 624.546=81.6714*2+k | | 81.6714=624.546*2+k | | x^3-24x^2+65x-42=0 | | 1270.444=6.28*r^2+6.28*r*21.9 | | 285.9912=6.28*r^2+6.28*r*5.3 | | (3n^2)(5n^3)(2n)= | | 41=5p+11 | | 41+5p=11 | | 16x+5x=8x-5 | | n-1.6n+2.2=-4(n+5.4) | | 4.8+8.5x=x+15.7 |

Equations solver categories